Pelatihan Pembuatan Pop-Up Book Sebagai Media Pembelajaran IPA Bagi Guru SD Kristen Upunyor - Lestari Lestari; Renny Souhoka; Ince Wattimury; Korneles Tuamain; Jecklin M. Lainsamputty; Sefanya Sairiltiata; Brain Moriolkosu; Yenliy Paliaky; Galfen Salow (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Pop-up book is one of the learning media that can be used by teachers in carrying out learning in class. This media is an innovative medium in the world of education so that training is needed for teachers to be able to create and apply it in school subject matter. This service aims to improve the skills and creativity of elementary school teachers in teaching through training in making pop-up books. This media is effective in attracting interest and facilitating students' understanding of subject matter, this service program is expected to facilitate more interactive and interesting learning. This training consists of delivering material related to learning media, pop-up book material, training on making pop-up books and questions and answers. This activity was held on June 6 2023 at Upunyor Christian Elementary School. The result of this activity is that pop-up book training activities can improve the quality of teaching in elementary schools and enrich the learning methods used by teachers.